Modern Analysis of The Comorbid Association with Cardiovascular Diseases - Urinov O. U. (Scholars Digest Publishing, 2024)
Based on the conducted research on the comparison of gender differences in comorbid pathology in patients with stable coronary artery disease (CHD), significant aspects related to cardiovascular diseases have been identified. The analysis showed that the average age of women with coronary heart disease exceeds the average age of men (64 years compared to 59 years), accompanied by a higher average body mass index (30.2 vs. 29.4 kg/m2). It was noted that men were more likely to become smokers (16.8% vs. 1.6%), and postinfarction cardiosclerosis was more common in them (61.8% vs. 50.4%). On the other hand, women had a higher prevalence of hypertension (99.2% vs. 97.8%) and atrial fibrillation (12.8% vs. 8.8%).
Keywords: Comorbidity, cardiovascular diseases, statistical analysis, association, diabetes mellitus, X2 and R methods, risk prediction, patients, treatment strategies, medical practice.